2013
DOI: 10.4028/www.scientific.net/amr.744.339
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of the Al-Ti-B/Al-Sr Modification on the Microstructure and Properties of the Hypereutectic Al-Si Alloy in Automotive Piston

Abstract: By using some types of means such as Optical Microscope (OM), Scanning Electron Microscopy(SEM), the testing of tensile mechanical properties and the testing of friction and wear, the impacts of the Al-5Ti-1B and Al-20Sr modification on the Al-16Si-4Cu-0.5Mg-0.2Mn alloy microstructure, mechanical properties and friction properties are researched. The results turn out that the modification can significantly refine the primary silicon and the eutectic silicon in the alloy, the Al-5Ti-1B mainly refined the primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 18 publications
0
2
0
1
Order By: Relevance
“…Under the action of stress, the cracks will further expand, reducing the strength and plasticity of the material. If the second phase is uniformly distributed with small and well-rounded shape in the α-Al matrix, the effect of dispersion strengthening can be generated, so that the strength and toughness of samples can be improved [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Under the action of stress, the cracks will further expand, reducing the strength and plasticity of the material. If the second phase is uniformly distributed with small and well-rounded shape in the α-Al matrix, the effect of dispersion strengthening can be generated, so that the strength and toughness of samples can be improved [25,26].…”
Section: Resultsmentioning
confidence: 99%
“…Under the action of stress, the cracks will further expand and reduce the strength and plasticity of the material. If the second phase is uniformly distributed with small and well-rounded shape on the α-Al matrix, the effect of dispersion strengthening can be generated, so that the strength and toughness of samples can be improved [28,29]. Si phase was fully diffused and dissolved after solid solution, the roundness of which was improved.…”
Section: Methodsmentioning
confidence: 99%
“…positively affect hardness and strength properties of Al-Si alloys. 513 Cu, Mn, Mg, and Zn additions cause the improvement of mechanical properties due to the solid solution hardening mechanism and/or secondary phase precipitation, Sr, B, Na, Ti, and V grain refinement mechanism. In a recent study, 14 it was revealed that the hardness and mechanical properties of binary Al-9Si alloy produced with permanent mold casting method can be improved even more with 0.1wt.% Sr and/or 0.1wt.% Sr + 0.6wt.% Mg additions, and presented new ternary Al-9Si-0.1Sr and quaternary Al-9Si-0.1Sr-0.6Mg alloys produced with this casting method.…”
Section: Introductionmentioning
confidence: 99%